Redesigning emergency patient flow with timely quality care at the Alfred. (13th January 2015) - Lowthian, Judy; Curtis, Andrea; Straney, Lahn; McKimm, Amy; Keogh, Martin; Stripp, Andrew
Abstract Objectives The 4 h National Emergency Access Target was introduced in 2011. The Alfred Hospital in Melbourne implemented a hospital‐wide clinical service framework, Timely Quality Care (TQC), to enhance patient experience and care quality by improving timeliness of interventions and investigations through the emergency episode and admission to discharge in 2012. We evaluated TQC's effect on achieving the National Emergency Access Target and associated safety and quality indicators. Methods Retrospective analysis with piecewise regression of 215 125 ED attendances before/after implementation, November 2009 to August 2013; with comparison of proportions of patients discharged, admitted or transferred from ED within 4 h of arrival; left at risk; unplanned ED re‐attendances up to 28 days; ED length of stay; and in‐hospital mortality. Results The percentage of patients admitted, discharged or transferred within 4 h rose from 60% in 2010, to 74% in 2013. Median ED length of stay decreased significantly. Rate of unplanned ED re‐presentations decreased by 27%, 22% and 17% within 24 h, 48 h and 7 days, respectively; and patient numbers leaving at risk halved from 8% to 4%. Mortality for admitted patients declined from 3.5% to 2.2%. All results were statistically significant. Conclusions and future directions TQC resulted in improvement in timeliness of care for emergency patients without compromising safety and quality. Success is attributed to effective engagement of stakeholders with a hospital‐wide approach to redesigning the care pathway and establishing a new set of principles that underpin care from the time of ED arrival.